COMMUNITY PERCEPTION TOWARDS IMPLEMENTATION OF WATERSHED NORMALIZATION POLICY THE CASE OF: LAVA FLOOD DISASTE R POST MERAPI ERUPTION 2010 IN SLEMAN, YOGYAKARTA - , Muhammad Umar Said ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Study about implementation of disaster policy in Indonesia is limited. On other hand, Indonesia is one of the countries susceptible to natural disasters, particularly earthquakes and volcanic eruptions. From several volcano eruption disasters, the eruption of Merapi in 2010 is one of the severe disaster especially lava flood disaster. The lava flood is the most damaging disaster which still continues strongly affects the watershed areas and the residentsâ settlement after the eruption. The lava flood requires efforts to normalize watershed from the overflow of volcanic materials. Based on the disaster case, the local government of Sleman Regency has issued the emergency regulation, namely, a watershed normalization policy. This is a policy to manage a process to recover the watershed to its normal condition. As an emergency policy, it requires an assessment and review of its implementation, especially the perceptions of the communities that were affected by lava flood disaster. By knowing the perception, the level of concordance between the content of the regulation and its actual implementation can be identified. That is why this study analyzes how the community perception towards the policy implementation. This study conducted in the most severe location of lava flood disaster in Gendol Watershed, Manggong and Kepuh Sub Village, Kepuharjo, Cangkringan, Sleman, Yogyakarta, Indonesia. This study uses primary data by questionnaire and secondary data by in-depth interview, reports, articles, and other data sources. Questionnaire data was taken by survey to the local community in Kepuharjo as respondents which were selected by systematic random sampling. Total respondents are 60